Agricultural Environmental Management Strategy - UNDANG KURNIA; NONO SUTRISNO (Indonesian Center for Agriculture Land Resource Development, 2008)
Developments in Indonesia has raised several positif impact for most people due to gaining the new opportunity jobs. However, these positive opportunity often raised negative impact, especially on land resources and the environment, and people surrounding. Development industries on productive agriculture land have decreased agricultural areas, pollution of soil, water bodies/rivers, and cheerfulness and health of people and other humanlife. Mine activities also caused negative impact such asdegradation of land resources and environment, and pollution due to the application of chemical matterial on sevaration of mine products. Land clearing for infrastructures construction (roads, buildings, bridges), and agricultural practices had caused land degradation and the environment, and pollution as well. The disturbance of natural resources and environmental imbalance caused the deterioration of soil productivity, and the quality of agricultural yield due to chemical contamination on soil, rivers/water bodies, and crops. These condition has to consider necessary effort on the agricultural and environmental management more precised,directed, and accurated. Therefore, identification and characterization of sources of degradation and pollution, and analyses on issues raised in the field to form strategic effort on agricultural environmental management. The deterioration of soil productivity could be managed by applying soil conservation and land rehabilitation techniques through integrated management of related governments, institutions, and farmers/people. The pollution on soil and plant need quality standard criterium for heavy metals, and the values could be determined and difined for Indonesia condition. Critical levels of heavy metals in the soil could be used as a guide for implementation of law imporcement. Industrial waste which is polluted rivers and water bodies could be easly predicted, due tospesific industry resulted chemical contents of liquid waste similar with content of raw materials. Inappropiate land management could accelerate increasing green house gases in the atmosphere, and would be caused global warming as well. Excessive carbondioxide emission could be controlled by sequistrated CO2 through revegetation and rehabilitation of degraded land. Methane (CH4) and nitrousoxide (N2O) emission from lowland rice could be controlled by reduction its planting areas and substitute by non rice commodites, appropiate and better water management, and slow release nitrogen fertilizer application.